Conventional and Sharia Perspectives on Returns in the Form of Candy and Illegal Parking Attendants - Sari Setyo Ningrum; Adil Indi Pebrian; Nurul Wahyuningsih; Aryani Beliana (Journal of Islamic Economy and Community Engagement, 2023)
Payment transactions at shops, minimarkets, or supermarkets, we as consumers have often experienced returns in the form of candy as a substitute for the remaining money paid. This of course raises various pros and cons between the cashier and the consumer, one of which is when the consumer refuses candy as a return for the remaining payment. The method used in carrying out this activity is Community-Based Participatory Research (CBPR). The purpose of this method is to provide education, provide an overview or example, and discuss information regarding Conventional and Sharia Perspectives on Returns Exchanged for Candy and Illegal Parking Attendants through social media platforms. The results of our campaign activities show that there are still many perspectives from the general public who do not know about whether or not it is permissible to exchange change for candy and how to refuse to pay illegal parking fees. It is hoped that by carrying out the social media campaign and interviews that we have created, the general public is aware of the importance of knowing how it is permissible or not to exchange change for candy and how to refuse to pay illegal parking fees.